ANALISIS STRATEGI PEMBIAYAAN MUDHARABAH DALAM PEMBERDAYAAN USAHA (STUDI BTM AMANAH BANGUNREJO) - Budi Suharto; Agus Hermanto; Anang Wahyu Eko Setianto (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
BMT (Baitul Maal Wat Tamwil) is a microfinance institution that serves as an intermediary between capital owners and recipients of capital. Therefore, the role of BMT needs to be further enhanced according to its function in collecting and distributing public funds, especially by paying more attention to financing to the productive economic sector, one of which is mudharabah financing. In this case, mudharabah financing is one of the financing used by BTM (Baitul Tamwil Muhammadiyah) Amanah Bangunrejo which is given to micro entrepreneurs in increasing their business. The problems discussed in this study are how is the mudharabah financing strategy in BTM Amanah Bangunrejo? And can the mudharabah financing strategy at BTM Amanah Bangunrejo empower businesses?. The purpose of this study is to describe and analyze the mudharabah financing strategy in empowering micro-enterprises. This research is descriptive qualitative, which describes and analyzes the problems raised. The data analysis technique in this study used descriptive qualitative data analysis. While the data collection techniques in this study used observation, interviews, and document retrieval. Based on the research, BTM Amanah Bangunrejo uses a business analysis strategy, a capital agreement and provision strategy, and a mentoring strategy. The mudharabah financing strategy has not been maximized in empowering micro-enterprises. Therefore, the researcher suggests that BTM Amanah Bangunrejo is more optimal in implementing the mudharabah financing strategy.